(untitled) (Balneo and PRM Research Journal, 2024)
This study aims to evaluate. in the course of one year. the role of physical therapy and occupational therapy intervention. in association of specific drug therapy versus only drug therapy. in patients with osteoporosis. The study was carried out between April 2022 and June 2024, on 94 patients with osteoporosis. selected from the Clinical Rehabilitation Hospital in Băile Felix. All subjects signed an informed consent form 46 subjects followed drug therapy, physical therapy and occupational therapy (study group) and 46 subjects had only drug therapy (control group). The following parameters were assessed: the decrease in height. bone mineral density (BMD) - the T score and the Qualeffo test for the quality of life. Between groups analysis showed that in the study group. The post-test values of the total Qualeffo score decrease significantly and showed a smaller decrease in height compared to control group. Regarding BMD there is no significant difference between the study group compared to control group. The results of the study suggest that a specific physiotherapy can cause significant improvements both of quality of life and vertebral static disorders. As far as BMD is concerned rehabilitation has only a limiting effect of braking its decrease.